An Interprofessional Education Panel on Development, Implementation, and Assessment Strategies - Kahaleh, Abby A. (Am J Pharm Educ, 2015)
This report provides a primer for implementing interprofessional education (IPE) within pharmacy and health sciences curricula. In 2013, a panel of administrators and faculty members, whose institutions offered IPE, funded by the Josiah Macy Jr. Foundation, shared best collaborative practice models at the American Association of Colleges of Pharmacy (AACP) Annual Meeting. These presenters subsequently collaborated to write a primer as guidance for other institutions interested in successfully implementing and continuously enhancing the quality of IPE programs. In this article, these IPE faculty members provide a rationale for creating IPE reforms, discuss successful strategies for innovative IPE programs, and share lessons learned for implementing effective assessment tools. A structure and process for determining outcomes of IPE models are presented and strategies for exploring shared education opportunities across health professions and for integrating top-down and bottom-up methods for IPE programs are given.